2010
DOI: 10.1128/cvi.00436-09
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial on the Safety, Tolerability, and Immunogenicity of MenACWY-CRM, an Investigational Quadrivalent Meningococcal Glycoconjugate Vaccine, Administered Concomitantly with a Combined Tetanus, Reduced Diphtheria, and Acellular Pertussis Vaccine in Adolescents and Young Adults

Abstract: This study evaluated the safety, tolerability, and immunogenicity of an investigational quadrivalent meningococcal conjugate vaccine, MenACWY-CRM, when administered concomitantly with a combined tetanus, reduced diphtheria, and acellular pertussis (Tdap) vaccine, in subjects aged 11 to 25 years. Subjects received either MenACWY-CRM and Tdap, MenACWY-CRM and saline placebo, or Tdap and saline placebo. No significant increase in reactogenicity and no clinically significant vaccine-related adverse events (AEs) oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 16 publications
2
51
0
2
Order By: Relevance
“…11 MenACWY-CRM (Menveo ® , Novartis Vaccines and Diagnostics) is a quadrivalent (A, C, W-135, and Y) meningococcal vaccine conjugated to CRM 197 , a nontoxic mutant of diphtheria toxin, as the carrier protein. 12 Previous phase 2 and 3 studies demonstrated that MenACWY-CRM elicited highly immunogenic responses and was well-tolerated in adults, [13][14][15] adolescents, 13,16,17 children, 18,19 and importantly, young infants. Background: Infants are at the highest risk for meningococcal disease and a broadly protective and safe vaccine is an unmet need in this youngest population.…”
Section: Introductionmentioning
confidence: 99%
“…11 MenACWY-CRM (Menveo ® , Novartis Vaccines and Diagnostics) is a quadrivalent (A, C, W-135, and Y) meningococcal vaccine conjugated to CRM 197 , a nontoxic mutant of diphtheria toxin, as the carrier protein. 12 Previous phase 2 and 3 studies demonstrated that MenACWY-CRM elicited highly immunogenic responses and was well-tolerated in adults, [13][14][15] adolescents, 13,16,17 children, 18,19 and importantly, young infants. Background: Infants are at the highest risk for meningococcal disease and a broadly protective and safe vaccine is an unmet need in this youngest population.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to previous studies examining co-administration of MenACWY-CRM and Tdap [16,17], non-inferiority criteria were met for all three pertussis antigens tested.…”
Section: Discussionmentioning
confidence: 58%
“…In the earlier studies, the direct comparators for Tdap immune responses were either Tdap alone [17] or Tdap administered with a placebo [16]. In contrast, the direct comparator group of the present study received a placebo with both Tdap and HPV4.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations